2009
DOI: 10.1038/sj.bjc.6605333
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EZH2 and Ki-67 in colorectal cancer and associations with treatment response and prognosis

Abstract: BACKGROUND: Enhancer of zeste homologue 2 (EZH2) is a member of the Polycomb group of genes that is involved in epigenetic silencing and cell cycle regulation. METHODS: We studied EZH2 expression in 409 patients with colorectal cancer stages II and III. The patients were included in a randomised study, and treated with surgery alone or surgery followed by adjuvant chemotherapy. RESULTS: EZH2 expression was significantly related to increased tumour cell proliferation, as assessed by Ki-67 expression. In colon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
120
3
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 19 publications
10
120
3
5
Order By: Relevance
“…a classical epigenetic view, the regulation of JMJD3 by 1,25(OH) 2 D 3 may be a mechanism to guarantee the correct activation of genes through the loss of the repressive H3K27me3 mark. Having in mind the requirement of JMJD3 expression for an adequate 1,25(OH) 2 D 3 action, the deregulation in human colon cancer of JMJD3 (downregulation) 37 and of the Polycomb gene EZH2 (overexpression) [74][75][76][77][78] may generate resistance to therapy with 1,25(OH) 2 D 3 and its analogs.…”
Section: Histone Demethylationmentioning
confidence: 99%
“…a classical epigenetic view, the regulation of JMJD3 by 1,25(OH) 2 D 3 may be a mechanism to guarantee the correct activation of genes through the loss of the repressive H3K27me3 mark. Having in mind the requirement of JMJD3 expression for an adequate 1,25(OH) 2 D 3 action, the deregulation in human colon cancer of JMJD3 (downregulation) 37 and of the Polycomb gene EZH2 (overexpression) [74][75][76][77][78] may generate resistance to therapy with 1,25(OH) 2 D 3 and its analogs.…”
Section: Histone Demethylationmentioning
confidence: 99%
“…Table 5 shows a detailed summary of all published studies reporting the association of EZH2 at the protein level with the tumor's clinicopathologic characteristics and outcome in carcinomas of different organs. With a few exceptions, 50,89,93,96 most published reports show that EZH2 overexpression is associated with higher histologic grade, more advanced clinicopathologic stage, and/or a higher risk of lymph node or distant metastasis. * Taking AJCC TNM staging as an example, a large proportion of the published literature (26 of 33 reports) demonstrated that EZH2 overexpression was correlated with more locally advanced disease and/or higher risk of lymph node or distal metastasis, while the remaining 7 reports showed no difference of EZH2 labeling in tumors with different TNM staging (as summarized in Table 5 61 However, Wagener and colleagues 63 were able to demonstrate a strong association between EZH2 expression on the one hand and high Fuhrman grade, advanced tumor stage, regional lymph node metastasis, and distant metastasis on the other.…”
mentioning
confidence: 99%
“…[15][16][17]19,24, This notwithstanding, conflicting studies exist that report either no prognostic value for EZH2 21,[89][90][91]93 or even an association with improved disease-free survival, 96 albeit to a more limited extent. Similarly, contradictory results have been reported in RCC: whereas Hinz et al 61 reported that the presence of elevated EZH2 mRNA levels is associated with low disease recurrence, Wagener et al 63 showed that patients with overexpression of EZH2 had decreased disease-specific survival.…”
mentioning
confidence: 99%
“…Samples for TMA construction were available for 409 of the 412 patients 20. In 39 cases, S100A4 staining was not technically successful, leaving a study population of 370 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The construction of TMAs has been described previously 17, 20. Sections from the TMAs were immunostained using the Dako EnVision Flex+ detections system (Dako, Glostrup, Denmark) as described previously 21.…”
Section: Methodsmentioning
confidence: 99%